Noise Enhanced Imaging of Weak Objects - Separa, Stephen Daedalus; Tapang, Giovanni; Lim, May; Saloma, Caesar (Science Diliman: A Journal of Pure and Applied Sciences; Vol 11 No 2 (1999), 2007)
A method that allows the imaging of weak objects is demonstrated through the use of additive noise. Additive noise (characterized using a variance parameter a) is used to drive the intensity of the test object so that a threshold detector detects it. Performing the simulation with a sufficiently large number of trials decreases the optimum value of noise required for a good image quality.
Keywords: noise dithering; image recovery